Desenvolvimento de métodos de determinação de tenofovir para aplicação em controle de qualidade e estudo de bioequivalência/ biodisponibilidade relativa - Maria Olivia Nogueira Teixeira (2011)
HIV, human immunodeficiency virus, is a retrovirus that affects the immune system of infected people. Overall global declines in the rate of new HIV infections and AIDS deaths hide important geographical differences in the size, temporal trends and modes of transmission of the HIV epidemics. In Brazil, from the beginning of epidemic, in 1980, until 2009, 592,914 cases of AIDS and 229,222 deaths due this disease were reported. In the history of HIV pandemic, Brazil was a pioneer due to the creation of a national program that allows the free distribution of antiretroviral medicines to those who live with AIDS. Tenofovir (TEN; 1-(6-aminopurin-9-yl) propan-2-yloxymethylphosphonic acid) belongs to the nucleotide analogue reverse transcriptase inhibitors class of antiretroviral. Actually, the costs of treatment with tenofovir have limited its use as first choice therapy in developing countries. The aim of the present work was to develop and validate analytical methods for quantification of tenofovir disoproxil fumarate (TDF) in pharmaceutical products and tenofovir in human plasma samples, in order to contribute to national manufacturing of the medicine. A sensitive high-performance liquid chromatography (CLAE) method coupled to UV detection was developed for the determination of TDF in tablets using C18 column (125 x 4.0 mm, 5ìm), detection at 260 nm and mobile phase containing triethylamine 0.1 % pH 5.3 solution: methanol (55:45). The proposed method has been validated with a linear range of 0.075 to 0.45 mg/mL, and demonstrated selectivity, accuracy, precision, ruggedness and matrix effect was not significant. A spectrometric UV method was developed for assessment of tablets dissolution using HCl 0.1 M solution as solvent and detection at 260 nm. The proposed method has been validated with a linear range of 0.0165 to 0.0495 mg/mL, and demonstrated selectivity, accuracy, precision, ruggedness and matrix effect was not significant.A CLAE method coupled to mass spectrometry and electrospray ionization in positive mode was developed for tenofovir quantification in human plasma. The chromatographic analysis was performed using a C18 column (100 x 4.6 mm, 5ìm) with mobile phase consisting of ammonium acetate 2 mM + 0.2% formic acid buffer: methanol (85:15) and involved solid phase extraction. The proposed method has been validated with a linear range of 5.00 to 600.00 ng/mL, and demonstrated selectivity, accuracy, precision and matrix effect was not significant. A bioequivalence study was performed using the developed method. It was a randomized, single-dose, open-label, 2-way, crossover study, fixed-dose single-tablet regimen, with 35 healthy adults and under fed conditions study. The evaluated products were considered bioequivalent and the geometric mean ratios (90% CI) for Cmax, AUC0t were 95.75 to 109.and 96.19 to 103.82, respectively